Aplicación de contabilidad en la empresa “telneting cia. Ltda”. De la ciudad de Quito, periodo: enero-junio/ 2013 - Molina Molin, Jheny Yolanda (2014)
The present research called “Accounting application in the company “Telneting Cía. Ltda.” in Quito City. the same that was proposed in order to enable the Company telneting count with a systematic registration of their operations by providing timely and reliable reports useful for decision-making, as well as a clear and concrete knowledge of the situation as it is economy of the Company. For the realization of the present thesis is complied with the objectives, began with the compilation of the source documents to support transactions and is ordered chronologically the existing documentation of the period January - June 2013, a plan was developed for specific accounts according to the activity of the company, was the implementation of a system of inventory control through a perpetual inventory system that allowed to know the cost of each article and the stop of the same, and applied the accounting process from the initial inventory until you get the financial statements, there were also the roles of payment of the employees. At the end of the application of the accounting process it was determined that in the exercise carried out during the period January - June 2013 utility was obtained, therefore it is recommended that the manager continue to apply the Accounting because it will allow you to get information quickly and efficiently to the actual situation of the company. At the end of the application of the accounting process it was determined that in the exercise carried out during the period January - June 2013 utility was obtained, therefore it is recommended that the manager continue to apply the Accounting because it will allow you to get information quickly and efficiently to the actual situation of the company.